Bodies bodies bodies - Reijn, Halina, 1975-; DeLappe, Sarah; Roupenian, Kristen; Herting, Ali; Hinojosa, David, 1976-; Stenberg, Amandla; Bakalova, Maria, 1996-; Herrold, Myha'la; Wonders, Chase Sui; Sennott, Rachel, 1995-; O'Malley, Connor, 1986-; Pace, Lee, 1979-; et al. (Lionsgate, 2022)
When a group of rich twenty-somethings plan a hurricane party at an isolated family mansion, a party game turns deadly in this fresh and funny look at backstabbing, fake friends, and one party gone very, very wrong.
Based on a story by Kristen Roupenian.
Originally released as a motion picture in 2022.
Wide screen.
Special features: Audio commentary with director Halina Reijn ; Who wants to play? making Bodies bodies bodies ; Deleted scenes.
Director of photography, Jasper Wolf ; editors, Taylor Levy, Julia Bloch ; music, Disasterpeace.
Amandla Stenberg, Maria Bakalova, Myha'la Herrold, Chase Sui Wonders, Rachel Sennott, Connor O'Malley, Lee Pace, Pete Davidson.
Keywords: Parties -- Drama; Young adults -- Drama; Hurricanes -- Drama; Games -- Drama; Murder -- Drama; Mansions -- Drama; Dark comedy films; Horror films; Slasher films; Feature films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities